ANALISIS KELAYAKAN USAHA KRIPIK RUMPUT LAUT UDANG EBI (STUDI KASUS DI UD. ORA ET LABORA KOTA MATARAM) - SUARTHA, I DEWA GEDE; WEDASTRA, MADE SUMA; HERLINA, SILFIA (GANEC SWARA, 2019)
In business, every expenditure issued aims to get benefits. Similarly, in the business of ebi shrimp seaweed chips at UD. Ora Et Labora Kota Mataram. In order for the resources used to be useful, the ebi shrimp seaweed chip business needs to be analyzed for its feasibility. While information on the business feasibility of ebi shrimp seaweed chips at UD. Ora Et Labora Kota Mataram is not yet available, so support from research is needed. Selection of UD. Ora Et labora of Mataram City as the location of the study was conducted by purposive sampling with a sample of three people which was also done by purposive sampling.     The results showed that the ebi shrimp seaweed chips business was feasible to be carried out by UD. Ora Et labora Kota Mataram with ROI = 35.33%; B / C = 1.11 and BEP = 181.78 packs.